Molecular dynamics study of pressure effect on crystallization behaviour of amorphous CuNi alloy during isothermal annealing - Kazanc, S. (Elsevier Science Bv, 2007)
The pressure effect on crystallization behaviour of amorphous CuNi alloys during isothermal annealing was studied by using molecular dynamic simulation method. Interaction between atoms in the model alloy system was calculated by Sutton-Chen type of embedded atom method. The structural phase transformation during isothermal annealing under different pressure values was analyzed based on the variations of the cohesive energy, unit cell volume and radial distribution functions (RDF). The obtained results show that the isothermal annealing of amorphous CuNi alloy causes a phase transformation from a metastable phase to a stable crystal phase and the increase of pressure during isothermal annealing increases the thermal stability of amorphous phase. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: isothermal annealing; embedded atom method; molecular dynamics simulation; rapid solidification